2011
DOI: 10.1590/s0004-28032011000400010
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced colorectal cancer: results of surgical treatment and prognostic factors

Abstract: -Objectives -To evaluate the incidence surgical results and prognostic factors of locally advanced colorectal cancer.Methods -Cohort study including 679 colorectal cancer patients treated from 1997 to 2007. Clinical, surgical and histological data were analyzed. Results -Ninety patients (females 61%; median age 59 years) were treated for locally advanced carcinomas (13.2%), either in the colon (66%) or rectum (34%). Extended resections most commonly involved the small bowel (19.8%), bladder (16.4%), uterus (12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
23
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 39 publications
6
23
2
3
Order By: Relevance
“…Metastatic patients were present in fewer than 20% of these series. The overall morbidity rate in this study was 37.1%, which is concordant with the results of other series (range 24-50%) 3,9-13. However, it is important to state that only 10% of patients in this study required surgical or image-guided intervention for these complications.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Metastatic patients were present in fewer than 20% of these series. The overall morbidity rate in this study was 37.1%, which is concordant with the results of other series (range 24-50%) 3,9-13. However, it is important to state that only 10% of patients in this study required surgical or image-guided intervention for these complications.…”
Section: Discussionsupporting
confidence: 90%
“…However, the two series with predominantly male patients reported morbidity rates of 24% and 50% 3,10. These results were not significantly different from those of studies not composed predominantly of male patients, such as the current study (morbidity ranged from 25-48%) 9,11-13.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Inclusion of clinical, surgical and pathological data capable of affecting survival suggested the role of several factors potentially implicated in oncological outcomes of these patients. Of note is the absence of influence of actual neoplastic adjacent organ invasion when compared to inflammatory adhesions in the study reported by Campos et al (2) . The most recent edition of the AJCC TNM classification system suggests subdivision T4 colorectal cancer that should definitively be considered in future studies.…”
mentioning
confidence: 73%
“…In the current issue of ARQUIVOS de GASTROENTEROLOGIA, a very interesting study on prognostic factors after radical surgery for locally advanced colorectal cancer by Campos et al (2) , brings up a series of aspects relevant to the current literature that deserve consideration.…”
mentioning
confidence: 99%